Potentiometric sensor for heparin polyion: transient behavior and response mechanism - Langmaier, Jan; Samcová, Eva; Samec, Zdeněk (Analytical chemistry, 2007)
Chronopotentiometry and electrochemical impedance spectroscopy were used to study the transient behavior and the potentiometric response mechanism of the polymer membrane-based sensor for heparin. Membrane with a composition of 66 wt % poly(vinyl chloride), 33 wt % o-nitrophenyl octyl ether (plasticizer), and 0.05 M tridodecylmethylammonium chloride (ion exchanger) was deposited on the surface of a silver or a glassy carbon (GC) electrode. In the latter case, the membrane contained also 0.1 M 1,1'-dimethylferrocene/1,1'-dimethylferricenium+ couple ensuring the electronic contact between the membrane and GC. The sensor was dipped in an aqueous solution of 0.1 M LiCl, which was stirred with a magnetic stirrer (2-18.2 Hz), and eventually spiked with heparin (0.05-5 U mL-1). Chronopotentiometric measurements were carried out using either the Ag supported membrane with a thickness>100 microm or the GC supported membrane with a defined thickness of 2-30 microm, which was also used in impedance measurements. Remarkable features of the potentiometric response include the linear dependence of the initial slope of the potential transient on the heparin concentration in the aqueous phase and on the square root of the stirring frequency, and the absence of the effect of the membrane thickness. Impedance measurements (0.1 Hz-10 kHz) made it possible to identify and to evaluate the geometric capacitance and the capacitance of the electric double layer at the membrane/solution interface, the bulk membrane and charge-transfer resistances, and the Warburg impedance of the chloride transport. Changes in the membrane bulk and charge-transfer resistances and the Warburg impedance upon spiking the aqueous solution with heparin were found to be consistent with the steady-state response of approximately -25 mV, indicating that the bulk chloride concentration in the membrane decreased to about half of its initial value. A novel theoretical model of the transient behavior was developed based on the balance of the charging and the faradic currents of chloride and heparin, in accordance with the ion-exchange mechanism that has been proposed previously. It was concluded that the initial slope of the potential transient is linked to the charging of the double layer coupled to the chloride ion transfer across the membrane/solution interface and to the diffusion-limited transport of heparin in the solution. The potentiometric assay of heparin could be based on measurements of the initial slope of the potential transient or the potential at a fixed time shortly after the heparin injection.
Keywords: kvartérní amoniové sloučeniny; Silver; membrány umělé; polyvinylchlorid; potenciometrie; Financing, Organized; elektrochemie; Ethers; Polyvinyl Chloride; elektrody; Potentiometry; ethery; uhlík; Carbon; Heparin; heparin; ionty; stříbro; Ions; Electrochemistry; Electrodes; Membranes, Artificial; financování organizované; Quaternary Ammonium Compounds